(untitled) (Journal of Applied Oral Science, 2015)
Periodontal ligament mesenchymal stem cells (PDLMSCs) are an important alternative source of adult stem cells and may be applied for periodontal tissue regeneration, neuroregenerative medicine, and heart valve tissue engineering. However, little is known about the impact of bacterial toxins on the biological properties of PDLSMSCs, including self-renewal, differentiation, and synthesis of extracellular matrix. Objective : This study investigated whether proliferation, expression of pro-inflammatory cytokines, and osteogenic differentiation of CD105-enriched PDL progenitor cell populations (PDL-CD105+ cells) would be affected by exposure to bacterial lipopolysaccharide from Escherichia coli (EcLPS). Material and Methods : Toll-like receptor 4 (TLR4) expression was assessed in PDL-CD105+ cells by the immunostaining technique and confirmed using Western blotting assay. Afterwards, these cells were exposed to EcLPS, and the following assays were carried out: (i) cell viability using MTS; (ii) expression of the interleukin-1 beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor alpha (TNF-α) genes; (iii) osteoblast differentiation assessed by mineralization in vitro, and by mRNA levels of run-related transcription factor-2 (RUNX2), alkaline phosphatase (ALP) and osteocalcin (OCN) determined by quantitative PCR. Results : PDL-CD105+ cells were identified as positive for TLR4. EcLPS did not affect cell viability, but induced a significant increase of transcripts for IL-6 and IL-8. Under osteogenic condition, PDL-CD105+ cells exposed to EcLPS presented an increase of mineralized matrix deposition and higher RUNX2 and ALP mRNA levels when compared to the control group. Conclusions : These results provide evidence that CD105-enriched PDL progenitor cells are able to adapt to continuous Escherichia coli endotoxin challenge, leading to an upregulation of osteogenic activities.